Competition of Forest Products Industry during to European Union Membership - Akyüz, Kadri Cemil (Bartın Üniversitesi, 2006)
Countries had put on the spotlight different economical formations and unions to meet the stronger configuration in competition environment, increasing and intensifying with globalization. These formations provided that the member countries exceeded the other countries in world market and these formations fascinated the countries for membership. European Union is one of the most effective unions. Our country's production potency and foreign trade potential should be examined and our commercial situation according to the member countries should be evaluated in EU, Turkey wants to occur in, possess trade volume is formed by the Customs Union effect and property of directing the markets. It was aimed that production, export and import figures of 12 different product groups in lumber, wooden panel and paper products of the forest products industry which possess an important situation in manufacturing industry formation are compare with 25 different EU countries and in this direction, figures of 15 years had been evaluated with multiple dimension methods which are hierarchical cluster and discriminate analysis for periods being 1990-1995, 1996-2004 and 1990-2004 The results showed that Customs Union ensure a positive contribution to panel industry's development and Turkey has got  competition power against the countries of union in this area; paper and lumber industries had been affected negatively after Customs Union and Turkey has got lower competition power in these areas.

Küreselleşme ile yoğunlaşan ve artan rekabet ortamı içerisinde ülkeler, daha güçlü bir yapıya kavuşabilmek için farklı ekonomik oluşumları ve birlikleri gündeme getirmişlerdir. Bu  yapılanmalar üye ülkelerin, olmayanlar karşısında dünya piyasalarında daha ön plana geçmelerini sağlamış ve ülkeleri üyelik süreçlerinde bir yarış ortamına sürüklemiştir. Oluşturulan en etkili birlikler sıralamasında Avrupa Birliği, kendine ön sıralarda yer bulmaktadır. Gümrük Birliğinin etkisi ile oluşturduğu ticaret hacmi ve piyasalara yön verebilme özelliği ile Türkiyeninde içerisinde yer almak istediği Avrupa Birliği genelinde ülkemizin sahip olduğu üretim gücü ve dış ticaret potansiyeli incelenmeli ve üye ülkelere göre sahip olunan ticaret konumu değerlendirilmelidir. Buçalışmada imalat sanayi yapılanmamız içerisinde önemli bir yere sahip olan orman ürünleri sanayi sektörünün Kereste, Ahşap Levha ve Kağıt ürünleri bazında 12 farklı ürün grubunun üretim, ihracat ve ithalat değerlerinin 25 farklı Avrupa Birliği ülkesi ile karşılaştırılması amaçlanmış ve bu doğrultuda Gümrük Birliğinin etkisinde incelenebilmesi için 15 yıllık veriler 1990–1995, 1996–2004 ve 1990–2004 yılı periyotları için ayrı ayrı çok boyutlu yöntemlerden Aşamalı Küme ve Ayırma (Discriminate) analizi yardımları ile değerlendirilmiştir. Çalışma sonucunda Gümrük Birliğinin Levha sanayin gelişimine olumlu bir katkı sağladığı ve bu alanda Türkiye'nin birlik üyeleri karşısında rekabet gücünün bulunduğu, Kağıt ve Kereste sanayilerinin ise GümrükBirliği sonrasında olumsuz etkilenmiş oldukları ve bu alanlarda Türkiye'nin rekabet gücünün düşük olduğu tespit edilmiştir.
AVRUPA BİRLİĞİ SÜRECİNDE TÜRKİYE ORMAN ÜRÜNLERİ SANAYİNİN REKABET DÜZEYİ